Impacts of collaboration networks, operational performance and reverse logistics determinantson the performance outcomes of the auto parts Industry - Phasit Phoosawad; Wanno Fongsuwan; Wawmayura Chamsuk; Josu Takala (My University, 2023)
The objectives of this study were to develop a framework of the collaboration network, operational performance, and reverse logistics determinants on the performance outcomes of the auto parts industry, and to study the direct, indirect, and overall effects of the factors that influence the performance outcomes of the auto parts industry.This quantitative research utilized a questionnaire as the tool for data collection, which was completed by the managers in the auto parts industry from 320 companies.According to the analysis with the Structural Equation Modeling (SEM), it was found that the collaboration networks, operational performance, and reverse logistics positively affect the performance outcomes; whereas, the collaboration networks mainly affect the development of organizations by causing performance outcomes to continue growing unceasingly, including the enhancement of sustainable competitive capacity and the operational results of the auto parts industry.
Keywords: Reverse Logistics; Auto industry; Quality and Supply Management